An Efficient Preparation of Novel Epoxyketone Intermediates for the Synthesis of Carfilzomib and Its Derivatives. (February 2016) - Du, Xiao; Zhang, Hao-yang; Lei, Meng; Li, Zi-yuan; Zhu, Yong-qiang
A novel and efficient preparation of epoxyketone intermediates for the synthesis of carfilzomib and its derivatives has been developed. Compared to reported methods, this highly stereoselective, environmentally friendly, low-cost method can be used in scaling up the synthesis of carfilzomib and its derivatives.